ПРАВОВЫЕ ОСНОВЫ ЭКОЛОГИЧЕСКИ УСТОЙЧИВОГО РАЗВИТИЯ - Lapteva, N.G. (Journal of actual problems of jurisprudence, 2019)
In given article to be told about a transition legal status to the concept of a sustainable development and its ecological bases.